2021
DOI: 10.4103/lungindia.lungindia_128_20
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cytology, acid-fast bacilli smear, gene Xpert and mycobacterial cultures in endobronchial ultrasound-transbronchial needle aspiration aspirate in diagnosing mediastinal tuberculous lymphadenitis

Abstract: Background: Diagnosis of isolated mediastinal tuberculosis (TB) can be challenging. Endobronchial ultrasound (EBUS) increases the diagnostic yield by direct sonographic visualization of mediastinal and hilar lymph nodes. With the advent of molecular techniques such as Gene Xpert, their addition to the cytology and cultures increases the diagnostic yield and detection of rifampicin resistance (RR) which helps change the effective therapeutic regimen immediately. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The combination of EBUS and contrast-enhanced chest CT to select promising nodes for biopsy has made this technique increasingly more precise, with enhanced sensitivity, specificity, and accuracy. Many studies worldwide have examined the sensitivity, specificity, and safety of EBUS-TBNA for diagnosing mediastinal large lymph node etiology, demonstrating its superiority and highlighting the integral role of this technique in clinical contexts, in addition to describing its development potential [13] , [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of EBUS and contrast-enhanced chest CT to select promising nodes for biopsy has made this technique increasingly more precise, with enhanced sensitivity, specificity, and accuracy. Many studies worldwide have examined the sensitivity, specificity, and safety of EBUS-TBNA for diagnosing mediastinal large lymph node etiology, demonstrating its superiority and highlighting the integral role of this technique in clinical contexts, in addition to describing its development potential [13] , [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinoscopy is rarely used because it is a difficult and invasive technique associated with many complications [13 , 14] . Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), in which bronchoscopy is guided by a bronchial pressure ultrasound (EBUS) to biopsy mediastinal lymph nodes through the bronchial wall, is increasingly being used in developing countries [14] , [15] , [16] . The National Lung Hospital was the first hospital specializing in the treatment of TB and lung diseases in Vietnam to apply this technique.…”
Section: Introductionmentioning
confidence: 99%
“…282 potential studies were selected for screening, 48 were suitable for full-text review and, then, 40 articles were excluded. A total of 8 studies [13,17,[20][21][22][23][24][25] met the inclusion criteria (Fig. 1).…”
Section: Overview Of Literature Searchmentioning
confidence: 99%
“…The 8 selected articles were published between 2014 and 2021 [13,17,[20][21][22][23][24][25]; they describe studies carried out between 2010 and 2018 (Table 1). The epidemiological design of these observational studies was clearly reported in all studies: 2 (25%) were cross-sectional [17,22], 1 (12.5%) was prospective [20], and 5 (62.5%) were retrospective cohort studies [13,21,[23][24][25].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation